Securing IoT and big data : next generation intelligence - Saravanan, Vijayalakshmi; Anpalagan, Alagan; Poongodi, T.; Khan, Firoz (Boca Raton : CRC Press, 2021)
"This book covers IoT and Big Data from a technical and business point of view. The book explains the design principles, algorithms, technical knowledge, and marketing for IoT systems. It emphasizes applications of big data and IoT. It includes scientific algorithms and key techniques for fusion of both areas. Real case applications from different industries are offering to facilitate ease of understanding the approach. The book goes on to address the significance of security algorithms in combing IoT and big data which is currently evolving in communication technologies. The book is written for researchers, professionals, and academicians from interdisciplinary and transdisciplinary areas. The readers will get an opportunity to know the conceptual ideas with step-by-step pragmatic examples which makes ease of understanding no matter the level of the reader"--
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things; Big data; Internet of things -- Security measures; Big data -- Security measures; TECHNOLOGY / Manufacturing; COMPUTERS / Machine Theory; COMPUTERS / Internet / Security